Separation and purification of low-molecular-weight chondroitin sulfates and their anti-oxidant properties - Wang, Jinpeng; Zhang, Lian; Jin, Zhengyu (Bangladesh Journal of Pharmacology, 2016)
Low-molecular-weight chondroitin sulfate was obtained by degradation of chondroitin sulfate using hyaluronidase. Then, separated with sephadex G25, DEAE-52, and finally purified with AKATA superpeptide separation system and fluorescence-assisted carbohydrate electrophoresis. The main compo-nents detected by high performance gel-filtration chromatography were disaccharide, tetrasaccharide, hexasaccharide with molecular weight of 521, 1024 and 1527 Da, respectively. The anti-oxidant activity of these three oligosaccharides in vitro showed that the reducing power (maximum value at 10 mg/mL) and superoxide anion radical scavenging abilities were increased (maximum value at 4 mg/mL) with an increased in their concentration. There were no significant differences of the anti-oxidant properties between those three oligosaccharides.